The Ecological Restructuring of Industrial Society requires Innovative Macroeconomic Concepts - Land, Rainer (Momentum Quarterly, 2016)
The debate on thinkable ways out of the current ecological crisis can be assigned to three fundamental discourses: (i) restructuring according to predominantly economic goals; (ii) post-growth discourse, i.e. on the reduction or even termination of economic growth; (III) Green New Deal-discourse which emphasizes the conversion by innovation and investment thrust under dominance of social objectives. In contrast to the New Deal of the Roosevelt administration of the 1930s, however, the contemporary Green New Deal discourse is still lacking a macroeconomic theory as well as a strategy. The focus should be the establishing of a principally novel type of industrial ecology, metabolically integrated into the ecosystems on earth. The reconstructing of social policy and social relationships should include the return to an income development oriented at the participation of all employees and a simultaneous change of consumption preferences and the usage of income compatible with environmental requirements. In order to support such a change, scientists should work out two specific environmental economic strategies: (i) for a complete public management of all ecological resources (energy, raw materials, ecosystems, ground, sinks); (ii) for the economic development of the industrial ecology by means of innovation cycles financed on credit as explained by Schumpeter.
Keywords: Environmental Economics; Green New Deal; Resource Management; Macroeconomics; Innovation Cycles